CATALYTIC AROMATIZATION OF NATURAL AND PETROLEUM GASES - Musayeva S.A.; Usanov F.Sh. (Journal of new century innovations, 2023)
Abstract: Hydrocarbon aromatization reaction, discovered in the 80s of the 20th century, is one of the rapidly developing and advancing directions of catalysis. As a result of the research conducted in a short period of time, a large number of effective catalysts were developed, which allowed to obtain C2- hydrocarbons with a yield of 30-35%. In this article, problems such as choosing a catalyst for the process of catalytic aromatization of natural and petroleum satellite gases, studying the laws of the reaction, modeling and optimization of the process are highlighted.